(untitled) (Texas Journal of Engineering and Technology, 2023)
One of the important factors affecting road safety is the choice of the optimum in terms of stability and handling of the car, speed of movement on rough roads. The loss of controllability of the vehicle can also occur at low speeds, which is much lower in terms of stability due to the insufficient stability of the wheels in contact with the road.